EARLY CRETACEOUS AMMONITES OF THE SIKHOTE-ALIN AND THEIR BIOSTRATIGRAPHIC AND BIOGEOGRAPHIC IMPLICATIONS - Sey I.I.; Kalacheva E.D. (My University, 2001)
Some Early Cretaceous ammonites nominally listed in the stratigraphic schemes and works on the Lower Cretaceous stratigraphy of the Sikhote-Alin are briefly described and pictured in this paper. Side by side with the ammonites, a succession of buchian assemblages is suggested for the recognized stratigraphic levels. The Barremian species Pseudohaploceras, being identified for the first time in the Sikhote-Alin, closely resembles ammonites of NE China. The new species P. chinense has been described regarding the materials obtained from China. The Early Cretaceous marine fauna of the Sikhote-Alin has been examined, in which ammonite assemblages are represented mostly by Tethyan species, whereas benthonic assemblages contain Boreal species defining an ecotone type of the marine communities of the area.
Keywords: Cretaceous; ammonites; Sikhote-Alin; Мезозой::Меловая; Mesozoic::Cretaceous